High-fat diet increases the level of circulating Monocyte Chemoattractant Protein-1 in Wistar rats, independent of obesity. (May 2021) - Syarif,; Rasyid, Haerani; Aman, Makbul; Lawrence, Gatot S.
Abstract: Introduction: Low-grade chronic inﬂammation has emerged as a key pathogenic link between high-fat diet (HFD)–induced obesity and the increased risk of chronic diseases. Evidence has shown that HFDs may induce inflammation in the central nervous system and peripheral tissues. Monocyte Chemoattractant Protein-1 (MCP-1) is a product of various cells that is known to be an inflammatory marker. This study investigated whether a HFD could induce obesity and increase the level of MCP-1 in Wistar rats. Methods: The Wistar rats were randomized into two groups: normal diet (ND) and HFD (n = 12 per group). Both groups were fed for 8 and 16 weeks, thus dividing the rats into 4 arms: ND8, ND16, HFD8, and HFD16 (n = 6 per sub-group). Obesity in rats was measured using the Lee index. Blood samples were taken to measure the level of MCP-1. Results: Our results showed that obesity did not occur in the group with a normal diet (ND8 and ND16). However, in the HFD group (HFD8 and HFD16), 4 of the 6 rats became obese. However, MCP-1 was significantly higher among non-obese rats in the HFD group compared with the ND group (p < 0.001). Conclusion: HFDs have been shown to increase the risk of obesity. In addition, increases in circulating MCP-1 were significantly different between Wistar rats given a HFD compared with the ND group. Highlights: Low-grade inﬂammation is a pathogenic link in high-fat diet (HFD)–induced obesity. Monocyte Chemoattractant Protein-1 (MCP-1) is known to be an inflammatory marker. HFD increases the level of circulating MCP-1 in Wistar rats.